TINJAUAN PELAKSANAAN REKONSILIASI FISKAL UNTUK MENGHITUNG PPh BADAN PT. RMA OLEH EMC - Rahmawati (2022)
PT. RMA is a company engaged in trading, namely buying and selling machines. Every tax year, PT. RMA is obliged to report its corporate tax liability. There is a difference in recognition of income and costs between the SAK and the Tax Provisions, thus requiring taxpayers to carry out fiscal reconciliation. Fiscal reconciliation of the commercial financial statements of PT. RMA needs to be reviewed. The purpose of this review is to find out what costs and income are corrected based on tax provisions and calculate the amount of income tax received by PT. RMA. The results of the discussion showed a difference in profit according to commercial and according to fiscal. Profit according to commercial is Rp 18.232.021.362. After fiscal reconciliation in accordance with tax regulations, positive corrections were obtained on the account of vehicle maintenance / repair costs, medical costs, vehicle insurance costs, entertainment costs, donation fees, tax burdens, and tax penalty burdens. While negative corrections are made to interest income accounts. So that taxable income or fiscal profit is obtained, which is Rp 20.852.481.190 and corporate income tax owed by PT. RMA in 2021 was Rp 4.587.545.820.